Pengaruh Aplikasi Plant Growth Promoting Rhizobacteria Terhadap Pertumbuhan, Hasil Panen dan Kadar Indole Acetic Acid Tanaman Kentang (Solanum Tuberosum L.) - Setyaningsih, Henni; Purwantisari, Susiana; Jannah, Siti Nur; Lunggani, Arina Tri (Jurnal Agroekoteknologi, 2024)
Potato (Solanum tuberosum L.) is a horticultural crop used as an alternative source of carbohydrates. The potato demand in Indonesia tends to increase yearly, but this does not align with its production. One of the efforts to increase potato production is fertilization. However, the intensive application of chemical fertilizers with increasing doses can damage the quality of the soil, kill microorganisms in the soil, and deteriorate the health of farmers. Therefore, it is necessary to conduct research to find alternative chemical fertilizers with the application of Plant Growth Promoting Rhizobacteria (PGPR) biological fertilizers. The study aimed to examine the application of PGPR to potato plants' growth, yield, and IAA levels. The sample has been taken in Kaponan Village, Pakis District, Magelang Regency. The field experiment method was a completely randomized design with four treatments and four replications. The treatments consisted of no application of PGPR, PGPR 40 mL 10 L-1 of water, PGPR 50 mL 10 L-1 of water, and PGPR of 60 mL 10 L-1 of water. The data were analyzed using the ANOVA test, and if there was a significant difference, the Duncan Multiple Range Test was continued at the 5% test level. The results showed a significantly different effect of PGPR application on growth and yields. The application of PGPR showed that the increase in IAA levels of potato plants was higher than without PGPR application. The best growth was obtained by treatment with PGPR application of 50 mL 10 L-1 of water. The PGPR application treatment of 60 mL 10 L-1 of water resulted in the best yields and the highest increase in IAA levels.